Dysregulated renal tubular handling of filtered glucose in patients with type 2 diabetes mellitus: a descriptive study - Zulfiqar, Asim; Jahan, Saira; Akbar Khan, Muhammad Nadim; Burney, Shamaila; Farooq, Muhammad; Fatima, Kiran (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the frequency of suspected dysregulated renal tubular handling of filtered glucose, and its association with blood glucose levels in type 2 diabetes mellitus. Method: The analytical, cross-sectional study was conducted from November 2022 to June 2023 at the Department of Medicine along with the Department of Pathology and Biochemistry, Pakistan Railway Hospital, Islamic International Medical College, Rawalpindi, Pakistan, and comprised diabetics aged 19-80 years. Blood and urinary glucose were assessed at the point of contact. Blood glucose 80-180mg/dl was considered glucose in range and >180mg/dl glucose above range. Hyper-function of sodium glucose transport receptors was suspected if urinary glucose was <++ and the function of these receptors was considered normal if urinary sugar was ++ or more. Association of suspected receptors and their association with blood glucose levels was determined. Data was analysed using SPSS 26. Results: Of the 159 diabetics, 91(57%) were females and 68(43%) were males. The overall mean age was 57±11 years (range: 46-68 years). Of the total, 43(27%) patients had glucose in range and 116(73%) had glucose above range. Of the diabetics with glucose above range, 54(47%) patients had hyper-functioning sodium glucose transport receptors, and 62(53%) had normal functioning sodium glucose transport receptors. Of the patients with glucose in range, 11(26%) had hyper-functioning sodium glucose transport receptors, and 32(74%) had normal functioning sodium glucose transport receptors. There was a significant association between sodium glucose transport receptors’ function and blood glucose levels (p<0.001). Conclusion: Dysfunction of sodium glucose transport receptors affected the secretion of glucose in the urine, resulting in impaired glucose regulation in type 2 diabetes mellitus cases. Key Words: Blood glucose, Diabetes, Glycosuria, Sodium-glucose transporter 2.